Comparative Analysis of the Labour Act Status of Seafarers in the Republic of Croatia and the Surrounding Countries of the Adriatic Sea - Vuković, Tony; Petrinović, Ranka; Siriščević, Ena (Transactions on Maritime Science, 2024)
The aim of this article is to present and compare the regulations concerning the specific labour act status of Croatian seafarers with those of seafarers in neighbouring countries that have access to the Adriatic Sea. These countries were part of the legal system of the former Socialist Federal Republic of Yugoslavia until the 1990s. The question of the professional and social status of seafarers is a specific and complex issue in Labour Act. Seafarers, as employees, have a distinct labour and social status compared to shore-based workers in many respects. To address this, the International Labour Organization (ILO) has adopted 68 instruments (conventions and recommendations) related to their labour status regulation. Today nearly all these ILO documents are consolidated in the 2006 Maritime Labour Convention, making it the most significant legislation concerning the work, life, and social rights of seafarers in international shipping. In this context, this paper examines and analyses Croatian national regulations governing labour and social status of seafarers. It also compares these regulations with those of the neighboring countries such as Slovenia, Montenegro, and Bosnia and Herzegovina, particularly in terms of the standards prescribed by Maritime Labour Convention.